Prevalence of hereditary cancer susceptibility syndromes in children with cancer in a highly consanguineous population. (August 2018) - Jastaniah, Wasil; Aljefri, Abdullah; Ayas, Mouhab; Alharbi, Musa; Alkhayat, Nawaf; Al-Anzi, Faisal; Yassin, Fawwaz; Alkasim, Fawaz; Alharbi, Qasim; Abdullah, Shaker; Abrar, Mohammed Burhan; Alsultan, Abdulrahman
Highlights: Hereditary cancer prevalence was 40% in 1742 children with cancer in Saudi Arabia. Parental consanguinity was the most frequent reason for cancer genetics referral. Consanguinity had no bearing on the median age of childhood cancer diagnosis. Lower leukemia and higher rhabdomyosarcoma frequency in children of consanguinity. The prevalence of Li-Fraumeni Syndrome was approximately 7% in our population. Abstract: Background & aim: Hereditary cancer susceptibility syndromes (HCSS) are reported in up to one-third of children with cancer. Diagnosis of HCSS is crucial for implementation of surveillance protocols. We identified children who fulfilled criteria for HCSS in Saudi Arabia using the American College of Medical Genetics and Genomics (ACMG) guidelines, addressing the utility of these guidelines in a highly consanguineous population. Methods: This multi-center cross-sectional study recruited 1858 children with cancer between January 2011 and December 2014. HCSS criteria were based on the ACMG guidelines. Results: Seven hundred and four (40.4%) out of 1742 eligible patients fulfilled criteria for HCSS. Consanguinity was reported in 629 (38%) patients, with 50 (2.9%) first-degree, 535 (30.7%) second-degree, and 272 (15.6%) third-degree relatives affected with cancer. Two hundred and eighty eight (17.4%) leukemia and 87 (5.3%) brain tumour patients fulfilled HCSS criteria, with parental consanguinity being the most frequent criterion in both (leukemia 85.4%, brain tumors 83.9%). However, leukemia was less frequent in patients of consanguineous parents ( p = 0.023). Conclusion: Four out of 10 children with cancer fulfilled criteria for HCSS, most often due to consanguinity. This higher than expected prevalence suggests the need to validate consanguinity as a criterion for HCSS in highly consanguineous populations.